Medicine at a glance - Davey, Patrick (At a glance, 2010)
The central title in the market-leading at a Glance series, Medicine at a Glance provides a concise and accessible introduction to the study of medicine and is the ultimate revision guide for the core medical curriculum. Ideal for medical students, Foundation Programme doctors and those training in the allied health professions, Medicine at a Glance presents each topic as clear, double-page spreads with key facts accompanied by tables, illustrations, photographs and diagrams.